A preharvest finishing procedure for Lemna to produce high levels of zeaxanthin that is retained post-high-light exposure - Marina López-Pozo; William W. Adams, III; Maureen McNamara; Barbara Demmig-Adams (Future Foods)
Development of a productive, nutritious, and low-input food source is needed for humanity's expanding population on Earth and for long-duration crewed space missions. The exceptionally protein- and micronutrient-rich members of the aquatic plant family Lemnaceae are uniquely suited for both purposes. We here introduce a protocol to accumulate large quantities of the carotenoid zeaxanthin that are retained post-high-light exposure. The function of the essential human micronutrients zeaxanthin, lutein, vitamin E (α-tocopherol), and pro-vitamin A (β-carotene) are briefly reviewed. Attention is given to the role of zeaxanthin in opposing oxidants (reactive oxygen species), the production of which is further enhanced by space radiation. We report a new preharvest finishing procedure – sudden transfer of Lemna plants grown in low light (200 µmol photons m-2 s-1) to high light (1000 µmol photons m-2 s-1) for six hours, which rapidly increased and stabilized zeaxanthin content. Unlike terrestrial crops, Lemna possessed a uniquely high protein content when grown in low light and did not experience any adverse effects of the abrupt five-fold increase in light intensity. These findings provide additional justification for Lemnaceae as food crops with applications on Earth as well as for future long-duration human space missions.